Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to show that the eigenvalues of the following integral equation \begin{align*} \lambda \phi(t) = \int_{-T/2}^{T/2} dx \phi(x)e^{-\Gamma|t-x|} \end{align*}

are given by \begin{align*} \Gamma \lambda_k = \frac{2}{1+u_k^2} \end{align*}

where $u_k$ are the solutions to the transcendental equation \begin{align*} \tan(\Gamma T u_k) = \frac{2u_k}{u_k^2-1}. \end{align*}

My approach was to separate this into two integrals: \begin{align*} \int_{-T/2}^{T/2} dx \phi(x)e^{|t-x|} = e^{-\Gamma t}\int_{-T/2}^t dx \phi(x)e^{\Gamma x} + e^{\Gamma t} \int_t^{T/2} dx \phi(x) e^{-\Gamma x}. \end{align*}

Then I differentiated the eigenvalue equation twice with this modification to find that \begin{align*} \ddot{\phi} = \frac{\Gamma^2-2\Gamma}{\lambda}\phi \end{align*} indicating that $\phi(t)$ is a sum of exponentials $Ae^{\kappa t} + Be^{-\kappa t}$ where $\kappa^2$ is the coefficient in the previous equation. Can anyone confirm this is the correct approach? I don't think there's any way to factor the original kernel and invert the result. And I'm having trouble determining the initial conditions of the equation to set $A$ and $B$. Assuming I can find these my instinct would be to plug $\phi$ back into the original equation and explicitly integrate and solve for $\lambda$.

share|cite|improve this question
    
I figured it out and thought I'd share the solution in case anyone else is plagued with this question. First of all there's a typo: it should read $\ddot{\phi} = -\frac{2\Gamma - \lambda\Gamma^2}{\lambda}$. To solve this you plug this back in to the original equation and evaluate when $t = 0$. Then you do the same for the equation $\lambda \dot{\phi}$ at $t = 0$. After simplifying you get the two separate solutions $\tan(\kappa T/2)=\frac{\Gamma}{\kappa}$ and $\tan(\kappa T/2) = -\frac{\kappa}{\Gamma}$. By messing around and using the double angle formula for $\tan(\theta)$ it's doable. – fatbox Nov 30 '11 at 9:28
    
In my previous comment I meant to say: $\ddot{\phi} = -\frac{2\Gamma - \lambda \Gamma^2}{\lambda}$ and I'm now defining $\kappa \equiv \frac{2\Gamma - \lambda \Gamma^2}{\lambda}$ and assuming an exponential solution: $\phi(t) = Ae^{i\kappa t} + Be^{-i\kappa t}$. When you plug in and check for $\phi(0)$ and $\dot{\phi}(0)$ you find the two equations I mentioned previously. You will find that one equation corresponds to $A = B$ and the other to $A = -B$. These are the symmetric and antisymmetric wavefunctions, which are analogous to the bound states of the finite square well potential. – fatbox Nov 30 '11 at 9:33

This problem was solved in Mark Kac, Random Walk in the presence of absorbing barriers, Ann. Math. Statistics 16, 62-67 (1945) https://projecteuclid.org/euclid.aoms/1177731171

share|cite|improve this answer
1  
While this link may answer the question, it is better to include the essential parts of the answer here and provide the link for reference. Link-only answers can become invalid if the linked page changes. - From Review – choco_addicted Jun 9 at 14:00

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.